Correlations between climatic conditions and foodborne disease. (February 2015) - Kim, Yong Soo; Park, Ki Hwan; Chun, Hyang Sook; Choi, Changsun; Bahk, Gyung Jin
Abstract: Climate change is likely to affect the incidence of foodborne disease outbreaks, but the relationship between foodborne disease and conditions of climate change is still poorly understood and may vary regionally. Therefore, this study investigated the relationship between climatic conditions/seasonal changes, with regards to temperature and relative humidity, and the incidence of foodborne disease outbreaks in South Korea during 2003–2012. Eight pathogens commonly associated with foodborne diseases were identified and the effect of changes in temperature and relative humidity on each of them was investigated. Pathogenic Escherichia coli had the strongest correlation with temperature and relative humidity (0.8998, 0.8803, p < 0.001), followed by Vibrio parahaemolyticus (0.6964, 0.8048, p < 0.05), Campylobacter jejuni (0.6595, 0.6142, p < 0.05), Salmonella spp. (0.7531, 0.3893, p = 0.005, 0.211), and Bacillus cereus (0.3556, 0.2040, p > 0.05). Norovirus had a strong negative correlation with temperature and relative humidity (− 0.9791, − 0.8747, p < 0.001), followed by Clostridium perfringens (− 0.6457, − 0.8635, p < 0.05). Staphylococcus aureus poorly correlated with both temperature and relative humidity (0.1106, − 0.1169, p > 0.05). The statistical model in the present study could be useful for estimating the prospective effects of climate change on foodborne disease patterns. Highlights: Different foodborne pathogens are affected differently by changes in temperature and relative humidity. Pathogenic Escherichia coli had the greatest impact on changes in temperature. Staphylococcus aureus were not significantly affected by either temperature or relative humidity